Simultaneous estimation of Ofloxacin and Cefixime in tablet form in presence of the inactive Ofloxacin USP Related compound A - Lobna A. Hussein; Emad M. Hussien; N. Magdy; Heba S. Mohamed (Faculty of Pharmacy, Cairo University, 2017)
A sensitive, precise and simple HPLC method have been developed, optimized and validated for the determination of Ofloxacin and Cefixime in presence of the inactive Ofloxacin USP Related compound A. Ofloxacin Related compound A is stated to be inactive thus its presence in the preparation will affect its potency. An isocratic separation was achieved using hypersil BDS C18 column with flow rate of 0.8 mL min−1 and UV detection at 294 nm. The mobile phase consists of 0.1 M ammonium acetate (pH 6.0 adjusted using glacial acetic acid) and acetonitrile in the ratio of (35:65, v/v). The method was linear over the range of 1.00 × 10−4 mg mL−1 to 0.1 mg mL−1 (r = 0.9999), 2.00 × 10−4 mg mL−1 to 0.1 mg mL−1 (r = 0.9998) and 1.00 × 10−4 mg mL−1 to 0.01 mg mL−1 (r = 0.9999) for Ofloxacin, Cefixime and Ofloxacin Related compound A, respectively. The limit of detection and quantitation for Ofloxacin Related compound A are 2.45 × 10−6 and 7.45 × 10−6 μg mL−1, respectively. The suggested method was validated in compliance with the ICH guidelines and was successfully applied for the quantification of Ofloxacin, Cefixime and Ofloxacin Related compound A in their commercial tablets. The method was also statistically compared to reference methods with no significant differences in performance.